Modified Jatropha nano-lubricant as metalworking fluid for machining process - Talib, Norfazillah; Abdul Sani, Amiril Sahab; Hamzah, Nur Adlisham (Malaysian Tribology Society, 2019)
Biodegradable oils that were derived from the nature are renewable sources that may substitute the petroleumbased and synthetic oils. However, the highly viscous Jatropha oil draws upon unsatisfactory lubrication performance in the machining process. Thus, in this study, the chemically modified Jatropha oils with and without the hBN nanoparticles additive were tested on an orthogonal cutting process as a metalworking fluid. The oil viscosity, cutting force (Fc), cutting temperature (Tc) and tool-chip contact length (Lc) are the criteria being evaluated. The results show that MJO+0.05wt.% hBN posed high viscosity index which correlates with the low Fc, Tc and Lc. This increases its potential for implementation as a green metalworking fluid for a sustainable machining process.